Formulasi,dan Karakteristik Mutu Fisik serta Evaluasi Nilai Sun Protection Factor Sabun Transparan Ekstrak Daun Sirih Merah - Yuniarti, Rafita; Nasution, Haris Munandar; Dachban, Syarifa Mayly B.; Putri, Nadya Iwani; Luthfianida, Arifna; Wahdaniati , Tri (Journal of Pharmaceutical and Sciences, 2025)
The sun emits ultraviolet radiation and can produce free radicals. If these free radicals continue to come into contact with the skin excessively, they can damage cells and eventually cause cancer. Sun Protection Factor (SPF) is a substance that protects the skin from ultraviolet rays. The capacity of a product to shield the skin is indicated by its SPF rating. Soap is a type of formulation that individuals frequently utilize. Red betel leaf extract can protect the skin from the harmful effects of free radicals and is expected to increase the soap's ability to protect the skin from exposure to sunlight and maintain skin health. The methods include making transparent soap, testing physical quality, and determining the sun protection coefficient at various red betel leaf ethanol extract concentrations. The result is a transparent black-green soap with a pH of 9, a foam height of 57-65 mm, and a water content of <15%. At a concentration of ethanol extract of 0%, the SPF value is 3, and the SPF values are 7.5 (10%), 12.28 (30 and 50%), 18.2 (70%), and 25 (90%). From this information, it can be inferred that clear soap created with red betel leaf extract possesses excellent physical attributes and effectively protects against sun exposure.